Exchange rate determination in Nigeria: Testing the monetary theory in the presence of asymmetries - Mohammed Musa Tumala; Ngozi Victor Atoi; Tari Moses Karimo (West African Journal of Monetary and Economic Integration, 2021)
This study examines the Nigeria Naira to US Dollar (?/) exchange rate determinants within the monetarist framework while accounting for potential asymmetric responses of the exchange rate to changes in money supply, real income, monetary policy rate, and inflation rate in Nigeria relative to the US. The study utilizes monthly data from 2010:M1 to 2019:M12. By applying a nonlinear autoregressive distributed lag (NARDL) model, the study shows that in the long-run, nominal exchange rate adjusts asymmetrically to relative money supply, real income, and inflation. However, the adjustment to relative money supply, is less than proportionate. The incomplete adjustment is attributed to CBN's intervention in the foreign exchange market. The study provides evidence that exchange rate adjustment is asymmetric only to changes in inflation in the short run. However, there is no evidence of asymmetry to the policy rate both in the short and long-run. Furthermore, monetary flexible exchange rate theory is effective in exchange rate determination only in the long run since all the variables are significant. For stronger Naira, the study recommends tight monetary policy stance, and that monetary authority should ensure that the domestic inflation does not go higher than that of her trading partners.
Keywords: F31; F41; 330; Exchange rate; interest rate; monetary theory; NARDL